Clinical characteristics and proposed mechanism of pediatric spinal cord injury resulting from backbend practice - Guo, Shuang; Gong, Huiming; Xu, Peipei; Xie, Yang; Yang, Degang; Liu, Zitong; Yang, Yuwei; Chen, Liang; Xie, Yongqi; Yang, Mingliang (Frontiers in Pediatrics, 2023)
Objective: Pediatric spinal cord injury without radiographic abnormality (SCIWORA) caused by backbend practice is increasing. This study proposed an underlying 'combined injury mechanism' related to the spinal cord and femoral nerve overstretching.Methods: Pediatric patients diagnosed with backbend-associated SCIWORA at the China Rehabilitation Research Center during 2017-2021 were recruited. Clinical and imaging data were collected, and each patient's clinical course and prognosis were determined. Healthy dancers were recruited to simulate the backbend, obtain images, and estimate the spinal cord and femoral nerve stretch ratio. A model for the 'combined injury mechanism' was established using 4-week-old SD rats.Results: Forty-two SCIWORA female patients with an average age of 6 (SD 1) years and an average hospitalization time of 91 (SD 43) days were assessed. The primary initial symptom was pain in the back and/or lower extremities (33, 79%). The average time from injury onset to severe paralysis was 2.0 (SD 0.6) hours. Most patients had complete paraplegia (32, 76%), and neurological levels were distributed mainly in thoracic segments (38, 91%). Patients with elicited tendon reflexes on admission tended to have an incomplete spinal cord injury (p=0.001) and improved motor recovery (p=0.018).After one year, the most common complications were scoliosis (31, 74%) and abnormal hips (14, 33%).Injury of the caudal spinal cord torn by nerve roots was confirmed by surgical exploration in a case.The thoracic spinal cord and femoral nerves were overstretched by 148.8±3.6% and111.7±4.0%, respectively, in a full backbend posture. The 'combined injury mechanism' was partially replicated in the animal model.: Spinal overstretch and transient dislocation are considered the primary mechanisms by which SCIWORA occurs in children. Overstretching the femoral nerve aggravates spinal cord injuries caused by backbend practice.